2013
DOI: 10.2337/dc13-1325
|View full text |Cite
|
Sign up to set email alerts
|

Is Neighborhood Green Space Associated With a Lower Risk of Type 2 Diabetes? Evidence From 267,072 Australians

Abstract: OBJECTIVELifestyle interventions for type 2 diabetes mellitus (T2DM) are best positioned for success if participants live in supportive neighborhood environments. Deprived neighborhoods increase T2DM risk. Parks and other "green spaces" promote active lifestyles and therefore may reduce T2DM risk. We investigated association between neighborhood green space and the risk of T2DM in a large group of adult Australians. RESEARCH DESIGN AND METHODSMultilevel logit regression was used to fit associations between med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
130
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(152 citation statements)
references
References 12 publications
15
130
2
Order By: Relevance
“…Comprehensive data on health, behavioral, socioeconomic and geographic aspects were collected using a questionnaire. After controlling for potential confounders, individuals living in greener surroundings have a significantly lower risk of diabetes and, particularly in women, of overweight and obesity, independently of physical activity and sitting time (82), in line with the findings of an earlier study on green environment and health (83). In addition, greener surroundings seemed to be linked to longer/better quality of sleep, and this association remained after controlling for psychological distress, physical activity and socioeconomic factors (84).…”
Section: Home and Its Surroundingsupporting
confidence: 77%
“…Comprehensive data on health, behavioral, socioeconomic and geographic aspects were collected using a questionnaire. After controlling for potential confounders, individuals living in greener surroundings have a significantly lower risk of diabetes and, particularly in women, of overweight and obesity, independently of physical activity and sitting time (82), in line with the findings of an earlier study on green environment and health (83). In addition, greener surroundings seemed to be linked to longer/better quality of sleep, and this association remained after controlling for psychological distress, physical activity and socioeconomic factors (84).…”
Section: Home and Its Surroundingsupporting
confidence: 77%
“…Prospective studies using objective measures of habitual sleep, over either longer and shorter periods of time, however, are needed to further explore this hypothesis. Given the positive impact of greenspace and the natural amenities on other health outcomes influenced by sleep such as diabetes, 69 our study has important implications for population-based health programs concerned with developing policies to improve the “outdoor” environment as a mechanism for reducing adverse health outcomes. 70 Additional factors (e.g., air quality) in the natural environment may be important to consider with respect to influences on sleep quality for racial ethnic groups, especially since we found that higher levels of exposure to positive attributes of the natural environment did not result in better sleep quality for Whites.…”
Section: Discussionmentioning
confidence: 97%
“…One study reported that the percentage of green space within a one or three kilometers of residence was associated with the perception of better overall health (Maas et al, 2006), and access to green space has been associated with improved health status, including lower body weight (Astell-Burt et al, 2013a; Pereira et al, 2013) lower risk of cardiovascular disease (Pereira et al, 2012), and diabetes (Astell-Burt et al, 2013b). Due to the complex relationship between socioeconomic factors, physical activity and green space (Lee and Maheswaran, 2011), it is challenging to determine the mechanisms underlying this association.…”
Section: Discussionmentioning
confidence: 99%